Impact of the Five-Year Intervention of an Antimicrobial Stewardship Program on the Optimal Selection of Surgical Prophylaxis in a Hospital without Antibiotic Prescription Restrictions in Costa Rica: A Retrospective Study - José Pablo Díaz-Madriz; Esteban Zavaleta-Monestel; Jorge Arturo Villalobos-Madriz; Carolina Rojas-Chinchilla; Priscilla Castrillo-Portillo; Alison Meléndez-Alfaro; Ana Fernanda Vásquez-Mendoza; Gabriel Muñoz-Gutiérrez; Sebastián Arguedas-Chacón (MDPI AG, 2023)
This study aims to characterize the impact of the implementation of an antimicrobial stewardship program (AMS) on the optimal selection of surgical antibiotic prophylaxis in adult patients. This is a retrospective quasi-experimental study that compared the selection and duration of antibiotics for all surgical prophylaxis prescriptions over six months, both before (pre-AMS) and after a five-year intervention of AMS (post-AMS). In addition, data related to the consumption of antibiotics, adverse drug reactions, and surgical site infections throughout the years of the intervention were analyzed. The rate of appropriate selection of antibiotic prophylaxis in surgical procedures improved to 80% during the post-AMS period. The percentage of optimal duration increased from 69.1% (N = 1598) in the pre-AMS period to 78.0% (N = 841) in the post-AMS period (p < 0.001). The consumption of ceftriaxone significantly decreased, while the use of cefazolin increased more than nine times. No severe adverse reactions or increases in surgical site infections were detected after the intervention. The implementation of an AMS in the surgical ward demonstrated a trend towards a positive overall impact on the selection and duration of prophylactic antibiotics for surgery, with positive results also observed in other variables associated with the prescription of these antibiotics.